A partially purified preparation of isolated chemosensory cilia from the olfactory epithelium of the bullfrog, Rana catesbeiana - Anholt, RR (J Neurosci, 1986)
Cilia at the tips of dendritic processes of olfactory receptor cells are the sites of initial recognition and transduction events in olfactory reception. We have detached cilia from the olfactory epithelium of the bullfrog, Rana catesbeiana, via a calcium shock and partially purified them in high yield (226 +/- 19 micrograms protein/frog, n = 14) by sucrose gradient centrifugation. The cilia appear to undergo osmotic lysis during the isolation procedure, forming isolated axonemal structures and ciliary plasma membrane vesicles with diameters of 100–500 nm and an internal volume of 2.3 +/- 0.5 microliter/mg protein. PAGE in SDS reveals approximately 30 protein bands, among which cytoskeletal components, such as tubulin and actin, are readily identifiable by immunoblotting. Approximately 15 glycoprotein bands reactive with concanavalin A are discernible with major glycopeptides at apparent molecular weights of 56–65, 95, and 116 kDa. In contrast to olfactory cilia, respiratory cilia, isolated from the palate of the frog, do not contain the prominent glycopeptides observed for olfactory cilia. The 56–65 kDa glycopeptide region reacts with antiserum against chick kidney, Na+/K+-ATPase, and contains the beta subunit of this enzyme. In addition, we have identified the alpha and beta subunits of a guanine nucleotide-binding protein (G-protein) in the olfactory cilia preparation. This preparation of isolated olfactory cilia from Rana catesbeiana represents a readily accessible model system for studies of initial events in chemosensory recognition and signal transduction in the olfactory system.